Henry, where have you lost your Self?. (October 2017) - Philippi, Nathalie; Roquet, Daniel; Ben Malek, Hédi; Noblet, Vincent; Botzung, Anne; Cretin, Benjamin; Blanc, Frédéric
Abstract: The Self is a complex construct encompassing distinct components, including episodic and semantic autobiographical memory, the Self-concept, and the subjective sense of Self, which highest level consists of Self-awareness. The neuro-anatomical correlates are complex, and it is debated as to whether a common region could support these different components of the Self, with a particular interest for the cortical midline structures and the medial prefrontal cortex (MPFC). Alzheimer's disease (AD) constitutes an interesting model for the study of Self as autobiographical memory typically deteriorates as the disease progresses. Here, we report the unexpected case of Henry, a patient with MCI due to AD who was unable to produce any personal autobiographical memories, nor describe his Self-concept, had a poor personal semantic memory, and disclosed unusual anosognosia for this stage of the disease. His cognitive performance was compared to a group of matched AD patients and a group of healthy controls confirming that the main components of his Self were degraded. We hypothesized that it was due to a marked atrophy within the cortical midline, as visually assessed on his MRI. We further elucidated these findings through Voxel-based morphometry analysis, which confirmed a significant atrophy of the MPFC that was specific to this patient. Moreover, this revealed significant atrophy within the bilateral insular cortex. Given the stage of the disease, the degradation of the Self is unlikely to be accounted for by deficient mnemonic processes, especially as the presence of discrete temporal atrophy was noted. We suggest that this specific pattern of MPFC and insular atrophy is responsible for the systematic collapse of the patient's Self, through the breakdown of the subjective sense of Self, which is proposed as a prerequisite to all other components, according to the model proposed by Prebble, Addis, and Tippett (2013).